2022
DOI: 10.5267/j.ijdns.2022.1.015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social media marketing on brand trust, brand equity and brand loyalty

Abstract: This study aims to determine the effect of social media marketing activities on brand trust, brand equity and brand loyalty in social media. The study uses the Structural Equation Modeling (SEM) method with SPSS 3.3.3 software with a sample of 450 respondents determined by the simple random sampling method who had experience of using social media for at least six months. Data was obtained by distributing online questionnaires using google form. The results show that social media marketing has a positive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 1 publication
5
39
0
9
Order By: Relevance
“…Qualtrics was utilized to create the questionnaire. Over the course of more than two months, a total of 570 valid questionnaires were collected by the simple random sampling method though online social media platforms based on research method suggested by Haudi et al . (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Qualtrics was utilized to create the questionnaire. Over the course of more than two months, a total of 570 valid questionnaires were collected by the simple random sampling method though online social media platforms based on research method suggested by Haudi et al . (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Content must be in line and consistent with the brand image, if the company's content is inconsistent, it will have an impact on decreasing trust [12]. Through social media marketing, Instagram can build perception among social media users and build positive brand image [29]. Thus, entertainment in social media marketing activities influence brand image to create positive image on consumer mind.…”
Section: Entertainmentmentioning
confidence: 99%
“…Trust constitutes a crucial element of successful and strong asso- Prior research confirmed the significance of brand trust in enhancing brand equity and demonstrated a strong relationship between brand trust and brand equity (Han et al, 2015;Haudi et al, 2022;Pandiangan et al, 2021). As a result, customer trust is important to determine brand equity (Ambler, 1997), and in turn, it has an exerts a potent effect on brand equity (Hu et al, 2010).…”
Section: Gbt Gbl and Gbementioning
confidence: 99%